Indonesian Political Populism in the Agrarian Sector - Faiz Kasyfilham (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
This article seeks to understand the role of populist ideology in marginalizing the agrarian sector and the agrarian populism movement in Indonesia in the Reformation Era. Indonesia is an agricultural country, so such marginalization and the limited involvement of the agrarian movement is ironic. Development studies see the marginalization of the agrarian sector as a consequence of the reorientation of economic development towards the industrial and service sectors, mostly in urban areas. Studies like this often do not look at the political side of the marginalization. This study aims to fill this gap by analyzing the phenomenon in Indonesia utilizing Margaret Canovan’s populist approach. The findings show the influence of political populism on the marginalization of the agrarian sector in the reformation era in Indonesia. Pragmatic, populist leaders exploited ‘the people’ as a political rhetorical tool to gain power without touching the agricultural sector where ‘the people’ reside.